The Reproductive and Seed Biology of Glycosmis pentaphylla (Rutaceae) - Y.M, Chan; A.L, Lim (Malaysian Journal of Science, 2007)
The floral, fruit and seed biology of Glycosmis pentaphylla (Rutaceae) was investigated. Anthesis occurred at 0700 - 1300 hours. Flower abortion was 27% and fruit abortion was 95%. Anther wall formation was of the basic type and pollen grains were shed at the 2-celled stage. Pollen grains are trizonocolporate, radio symmetric and prolate spheroidal. They showed maximum germination in 4% sucrose solution and lost their viability four days after anthesis. The coefficient of uniformity of germination for extracted seeds sown was 0.04 compared to 0.01 for intact fruits sown. Seed germination was less than 10% after storage in 5°C, 15°C and 28°C for 25 days although the viability of fresh seeds tested by germination was very high (97%). Seed germination is hypogeal and both fasciation and polyembryony occurred rarely.